Nilai-Nilai Aqidah Islam yang Terkandung dalam Novel Kembara Rindu Karya Habiburrahman El Shirazy - Intan Nurfauziah; Sobar Al Ghazal; Fitroh Hayati (Bandung Conference Series: Islamic Education, 2022)
Abstract. Nowadays value of aqidah has an important role for a person in living life, especially in the understanding and application of islamic religious values that he embraced. Aqidah value the main key for a person to live in harmony. Aqidah value can be obtained from anywhere, not only fixated on textbooks, but also can be obtained from literary works, one of which is novelsThis study aims to explore and analyze the values of aqidah and character typology contained in the Novel kembara rindu so that readers can understand and learn from the wisdom conveyed by the author. This research discusses the values of moral education contained in the novel of fouras the main characters, This research uses qualitative approach which is descriptive analysis approach, and using literature research method.The results of this study are moral values conducted by 4 main characters in the novel, one of which is Syifa who has an honest nature and Ridho who religious blessing and trust And also in the novel contained aqidah values such as,(1) such as taqarub to Allah such as praying, praying, blessing Allah, dzikir, istighfar and reading the Qur'an (2) Typology of characters in novels related to aqidah, such as hard workers, syaja'ah (brave), religious , honest and helpful (3) The implications of the values of aqidah in the novel of the longing traveler for a Muslim, such as praying, seeking religious knowledge, religious and gentle educators, broadcasting the Qur'an, covering aurat and loving orphans. Abstrak. Dewasa ini, nilai- nilai aqidah memiliki peranan penting bagi seseorang dalam menjalani kehidupan, terutama dalam pemahaman serta penerapan nilai-nilai agama Islam yang dianutnya. Nilai-nilai Aqidah dapat diperoleh darimana saja, tidak hanya terpaku kepada buku pelajaran, namun juga dapat diperoleh dari karya sastra, salah satunya adalah novel.Penelitian ini menggunakan pendekatan kualitatif yaitu pendekatan deskriptif analisis,Hasil penelitian ini adalah nilai-nilai aqidah yang dilakukan oleh empat tokoh utama di dalam novel, salah satunya dalah syifa yang memiliki sifat jujur dan ridho yang religius dan amanah. Dan juga di dalam novel tersebut terkandung nilai-nilai aqidah seperti, (1)seperti taqarub kepada Allah seperti berdoa,sholat, ridho Allah,dzikir, istighfar dan membaca Al-Qur’an(2)Tipologi tokoh di dalam novel yang berkaitan dengan aqidah, seperti pekerja keras, syaja’ah (berani), religius,jujur dan tolong menolong (3)Implikasi nilai-nilai aqidah dalam novel kembara rindu bagi seorang muslim,seperti menunaikan sholat,menuntut ilmu agama,pendidik yang religius dan penuh kelembutan,mensyiarkan Al-Qur’an, menutup aurat dan menyayangi anak yatim.